Peran Guru PAUD dalam Menstimulasi Perkembangan Bahasa Anak pada Kelompok B Usia 5-6 Tahun - Ninik Kustini (Universitas Muhammadiyah Gresik, 2024)
Teachers as the main actors in schools can have an optimal effect on children's language development. Language is a human tool for communicating with other humans. Teacher stimulation in child development needs to be considered in each method of giving it because it will have an impact on the child's life in the future. The aim of this research is to examine and determine the role of teachers in stimulating children's language development in group B at RAMNU 178 Nurul Huda. Methods of data collection carried out by researchers are using observation, interviews, and documentation. The type of research used in this study is a descriptive qualitative approach. Based on the research results, it can be explained that the teacher's role in stimulating children's language development can be by using reading, storytelling, listening and writing. Apart from this, teachers also need to motivate children so that the stimulus for children's language development develops well. Thus, it can be concluded that the role of teachers in stimulating children's language development is important so that children's Indonesian language development in the future can develop well through reading, speaking, listening and writing. And the teacher doesn't forget to provide motivation and the right technique for children's learning in the future. Keywords : the role of the teacher, children's language development